2009
DOI: 10.1111/j.1365-2923.2009.03412.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simulator training on clinical skills acquisition, retention and transfer

Abstract: Students can acquire and retain clinical skills with CRS training, but demonstrate limited ability to transfer these to other problems. Further studies are needed to explore ways of improving learning and transfer with CRS training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Several investigators have demonstrated that simulation-based medical education is effective in cardiac auscultation [12,14,15,17,19]. In contrast, others reported no significant differences in the proficiency in cardiac auscultation between learners trained by high-fidelity simulation and those trained by low-fidelity simulation or no intervention [13,16,18,20].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several investigators have demonstrated that simulation-based medical education is effective in cardiac auscultation [12,14,15,17,19]. In contrast, others reported no significant differences in the proficiency in cardiac auscultation between learners trained by high-fidelity simulation and those trained by low-fidelity simulation or no intervention [13,16,18,20].…”
Section: Discussionmentioning
confidence: 92%
“…Although technology-enhanced medical simulation is a useful tool for health professional learners to acquire a variety of knowledge and skills as well as desirable behaviors [11], its effectiveness in cardiac auscultation training is still controversial [12][13][14][15][16][17][18][19][20]. Furthermore, it is not known whether the effectiveness of auscultation training using a cardiology patient simulator differs among a variety of heart sounds and murmurs.…”
Section: Introductionmentioning
confidence: 97%
“…In a similar study, Fraser, Peets, Walker, Tworek, Paget, Wright, and McLaughlin (2009) conducted a medical students' training study using a cardiorespiratory simulator (CRS). While the simulator improved results when compared to students who did not use a simulator, students displayed only a limited ability to transfer skills learned to other real-world problems (Fraser et al, 2009). Lintern et al (1989) note in their study of ground attack bombing that decreasing physical fidelity does not always lead to a decrease in training transfer.…”
Section: The Debate Simulator Fidelity Does Not Affect Training Transfermentioning
confidence: 99%
“…Similar results have been reported for the retention of practical skills. In one study, students taking a retention test six weeks after receiving simulator training on the clinical management of chest pain and shortness of breath scored between 70% and 80% of the points they had achieved in a post-training directly after teaching [18]. Similarly, six-month retention rates of 64% have been reported for telephone referral skills [19].…”
Section: Discussionmentioning
confidence: 99%